(untitled) (Colombia Medica, 2011)
Objective: To evaluate the prevalence of cardiovascular risk factors (CRF) and absolute risk (AR) among first-degree consanguinity relatives of Colombian patients with hypertension. Methods: The study comprised 227 relatives (siblings and children of both sexes, between 12 and 40 years of age) and 204 hypertensive patients 34-84 years old from Quindío, Colombia. Lipid profile, glycemia, smoking, body mass index, and blood pressure were analyzed, and the AR of cardiovascular disease (CVD) to 10 years was estimated. Relatives were divided into two groups: GF1 relatives 18 years. Results: three or more CRF were found in the three groups. The prevalence for smoking was 20.1%, 9.1%, and 15.9% in patients, GF1, and GF2, respectively. Hypercholesterolemia was 42.2%, 15.2%, and 18.6% in patients, GF1, and GF2, respectively. The prevalence of low HDL-c levels was 50.5%, 44.9%, and 63.6% in relatives, GF1, and GF2, respectively. Obesity was present alone in patients, (32.4%) and GF2 (10.8%). The AR was 19.6 and 6.4 in male and female patients, respectively; 0.31 and 0 in GF1 females and males, respectively, and in GF2 it was 1.5 and 0.15 in males and females, respectively. Conclusions: Patients and relatives had more than three CRFs. HDL-c was low in all three groups. The AR was high in the young relatives. Programs are needed for weight, smoking, sedentary and dyslipidemia control to prevent or delay the development of CVD in relatives.